Self-healing type fire physical evidence logistics transportation buffer material and preparation method thereof

Through the self-healing buffer material formed by in situ polymerization in melamine sponge, the problem of the lack of flame retardant, adhesion and self-healing performance of fire physical evidence transportation buffer materials in the prior art is solved, and efficient fire physical evidence protection and transportation safety are achieved.

CN119708755AActive Publication Date: 2025-03-28SHENYANG FIRE RES INST OF MEM

Patent Information

Application Number
CN202510228239.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The existing fire physical evidence transportation buffer materials lack flame retardancy, adhesion and self-healing properties, resulting in fire physical evidence being easily damaged and lost during transportation, and there is a risk of secondary accidents.

Method used

A self-healing buffer material consisting of a melamine sponge, an imidazole compound containing a C=C bond, a silane compound containing a C=C bond and a Si-H bond, and an olefin compound containing at least two C=C bonds, is used to form a material with flame retardant, adhesion and self-healing functions in the pores of the melamine sponge through in situ polymerization.

Benefits of technology

This material has excellent flame retardant properties, which can effectively prevent secondary accidents caused by fire physical evidence; it has good adhesion and damping effect, reducing the probability of damage and loss of fire physical evidence; it has self-healing ability, repairing damage, and improving the number of recycling and economic benefits of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708755A_ABST
    Figure CN119708755A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of fire material evidence traceability, and particularly relates to a self-healing type fire material evidence logistics transportation buffer material and a preparation method thereof. Aiming at the problems that in the prior art, a buffer material for protecting fire material evidences is easy to damage, is not flame-retardant, cannot be self-closed and can cause confusion or loss of the material evidences, (4-vinylphenyl) dimethylsilane, 1-vinyl-3-butylimidazolium hexafluorophosphate ionic liquid and butadiene are used as raw materials, and are subjected to in-situ polymerization in pores of melamine sponge, so that the material evidences are formed; the buffer material with flame-retardant and self-healing functions is obtained by taking polymerization of the three raw materials as main materials and self-polymerization of the ionic liquid and butadiene as auxiliary materials, so that the possibility of scattering and losing of fire evidences is reduced, meanwhile, the cycle use frequency of the buffer material is greatly increased, and the buffer material is low in cost, convenient to popularize and use and good in economic benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fire evidence tracing, and in particular relates to a self-healing fire evidence logistics transportation buffer material and a preparation method thereof. Background Art

[0002] In 2022, a total of 825,000 fires were reported in my country, resulting in 2,053 deaths, 2,122 injuries, and direct property losses of 7.16 billion yuan. In the first half of 2023, a total of 550,000 fires were reported nationwide, resulting in 959 deaths, 1,311 injuries, and direct property losses of 3.94 billion yuan. Compared with the same period in 2022, the number of fires increased by 19.9% ​​and the number of injuries increased by 9.3%. It can be seen that the current fire situation in my country is still severe. After a fire case / incident occurs, physical evidence identification is usually required to confirm the cause of the fire, clarify the responsibilities of all parties, and summarize relevant lessons learned.

[0003] Unlike criminal investigation cases that require two people with police officer credentials to submit physical evidence for inspection on site, because there are few institutions in my country with relevant identification qualifications, more than 90% of fire evidence is sent for inspection via express / logistics mail. However, due to the characteristics of fire evidence itself - such as burning debris is fragile and easy to pulverize; metal wires, glass and other evidence have sharp fractures; grassroots investigators usually extract large quantities of physical evidence with large volumes and heavy weights, etc., and the external forces during transportation and sorting - most fire evidence will have its overall timing destroyed during the mailing process (such as burning lithium battery packs are destroyed and scattered during the mailing process, making it difficult to trace their positional relationship), and even the express packaging boxes are damaged, resulting in the loss of tiny evidence such as molten beads.

[0004] The significance of identification work is to assume that specific physical evidence extracted from the scene can ultimately be linked to the people, places or objects involved in the case. The premise of this work is that the physical evidence sent for inspection is traceable, that is, the physical evidence must not be damaged during the inspection process, and the relevance of the case elements can be achieved. For this reason, all parties have been arguing about the damage to the fire physical evidence during the mailing process, which has increasingly become a new growth point for judicial conflicts.

[0005] Using cushioning materials between the outer packaging box and the fire evidence is the preferred solution to reduce the chance of damage during the transportation of fire evidence. Existing cushioning materials mainly include expanded polystyrene, expanded polyethylene, polyurethane sponge, foam film, etc. However, the above cushioning materials are not suitable for the transportation protection of fire evidence. The main problems are: first, the above-mentioned buffer materials are not flame retardant. Certain fire evidence, such as incompletely discharged battery packs and combustion aid evidence, have the risk of secondary accidents. At this time, the more buffer materials are added, the more combustible materials there are, and the greater the risk; secondly, the above-mentioned buffer materials are not adhesive. On the one hand, they cannot better fix the fire evidence and limit its movement in the packaging box to reduce the chance of breakage. On the other hand, they cannot adhere to the damaged fire evidence and reduce the probability of loss of small key evidence such as molten beads; thirdly, the above-mentioned buffer materials do not have self-healing properties. After evidence such as glass with sharp fractures, iron bridge frame wreckage, and wires penetrate the buffer materials and are vibrated out of the damaged area, the buffer materials cannot close the gaps by themselves, which may cause confusion or loss of evidence. At the same time, the damaged materials cannot heal themselves to be repaired, that is, the materials cannot be recycled, causing a large amount of white pollution.

[0006] In view of this, it is necessary to develop a new generation of intrinsically safe fire evidence logistics transportation buffer materials to significantly reduce the risk of secondary fire accidents and the probability of damage to evidence, improve the traceability of evidence, reduce related judicial disputes, and increase the number of times the buffer materials can be recycled, thereby reducing the overall application cost. Summary of the invention

[0007] In order to solve the above problems existing in the prior art, the present invention provides a self-healing fire evidence logistics transportation buffer material and a preparation method thereof.

[0008] The self-healing fire evidence logistics transport buffer material of the present invention is mainly composed of melamine sponge, imidazole compounds containing C=C bonds, silane compounds containing C=C bonds and Si-H bonds, and olefin compounds containing at least two C=C bonds; wherein the imidazole compounds containing C=C bonds include 1-vinyl-3-butylimidazole hexafluorophosphate ionic liquid, the silane compounds containing C=C bonds and Si-H bonds include (4-vinylphenyl) dimethylsilane, and the olefin compounds containing at least two C=C bonds include butadiene; the buffer material also contains a solvent and a photoinitiator, wherein the solvent includes dichloromethane, and the photoinitiator includes Irgacure-2959.

[0009] The amounts of the materials in the buffer material are as follows: the molar ratio of (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate, and butadiene is (5-80): (10-90): (5-80); the mass of the melamine sponge in the buffer material accounts for 65%-80%.

[0010] The method for preparing the self-healing fire evidence logistics transport buffer material of the present invention comprises the following contents: Taking melamine sponge as the base material, a quantitative reaction liquid is dripped into it so that imidazole compounds containing C=C bonds, silane compounds containing C=C bonds and Si-H bonds, and olefin compounds containing at least two C=C bonds are in situ polymerized in the pores of the melamine sponge to obtain a fire evidence logistics transportation buffer material with self-healing and flame retardant functions.

[0011] The synergistic effect of the above-mentioned ionic liquid containing a large amount of flame retardant elements and the melamine sponge gives the new generation of fire evidence logistics transportation buffer material inherent flame retardancy; at the same time, the polymerization of (4-vinylphenyl) dimethylsilane with butadiene and ionic liquid is the main process, and the self-polymerization of the above-mentioned ionic liquid and the self-polymerization of butadiene are the auxiliary processes, which gives the new generation of fire evidence logistics transportation buffer material self-sealing performance and adhesion of the breach, which not only improves the damping and buffering properties of the buffer material for fire evidence, but also plays a role in the adhesion and preservation of detached fire evidence debris such as molten beads; after the buffer material is damaged, the strong hydrogen bonding between the silicon-hydrogen bond of (4-vinylphenyl) dimethylsilane and the imidazole matrix of the ionic liquid is used to make the breach heal automatically and repair the material.

[0012] The specific preparation method of the buffer material is as follows: S1. Dissolve (4-vinylphenyl)dimethylsilane and 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add butadiene and a small amount of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, and store it in an ice water bath.

[0013] The amounts of the materials used in this step are as follows: the molar ratio of (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate, and butadiene is (5-80): (10-90): (5-80); the total mass of the above three materials accounts for 50%-80% of the total mass of the reaction solution; the molar amount of the photoinitiator accounts for 1%-5% of the total molar amount of the above three materials plus the photoinitiator.

[0014] S2. Add the above reaction solution dropwise into the melamine sponge, slowly heat the system to room temperature after the sponge fully absorbs the reaction solution, place it under a UV lamp for 5 min to 10 min, and perform primary photopolymerization; replace the backlight side with the light-facing side, and perform secondary photopolymerization under a UV lamp for 5 min to 10 min; after aging in an oven at 50°C to 100°C for 3h to 8h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0015] The proportion of melamine sponge and reaction liquid in the buffer material was calculated by weight gain method, wherein the melamine sponge accounted for 65%~80% of the buffer material mass, and the reaction liquid accounted for 20%~35% of the buffer material mass.

[0016] The present invention has the following beneficial effects: The present invention uses commercially available melamine sponge as a carrier, and makes 1-vinyl-3-butyl imidazole hexafluorophosphate ionic liquid, (4-vinylphenyl) dimethylsilane and butadiene in the reaction solution in situ polymerize in the pores of melamine sponge at room temperature to obtain a fire evidence logistics transportation buffer material with self-healing and flame retardant functions. The buffer material has excellent flame retardant effect, is flame-retardant, self-extinguishing from fire, and drip-free, and can effectively prevent fire evidence from causing secondary accidents; it has good adhesion damping effect, which can not only greatly reduce the probability of fire evidence moving and impacting during transportation, but also play an adhesion preservation role for the debris of detached fire evidence such as molten beads, effectively preventing the loss of key small evidence; the buffer material can automatically repair the break after damage, has room temperature self-healing ability, reduces the possibility of scattered loss of fire evidence, and greatly increases the number of recycling times of the buffer material, and is low in cost and easy to promote and use, with good economic benefits. The above characteristics can greatly improve the safety and traceability of fire evidence in the express / logistics transportation process, and significantly reduce related judicial disputes. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of a method for preparing the buffer material of the present invention; Figure 2 This is a scanning electron microscope image of the buffer material prepared in Example 1; Figure 3 This is a test chart of the self-healing efficiency of the buffer material prepared in Example 3 at room temperature for 12 hours; Figure 4 This is a heat release rate spectrum of the buffer material prepared in Example 4; Figure 5 90° peel strength diagram of the buffer material prepared in Example 4 on different material surfaces; Figure 6 This is a graph showing the weight gain rate of the buffer material prepared in Example 5 over 30 days; Figure 7 90° peel strength diagram of the buffer material prepared in Example 5 on different material surfaces; Figure 8 This is a test chart of the self-healing efficiency of the buffer material prepared in Comparative Example 6 at room temperature for 12 hours. DETAILED DESCRIPTION

[0018] The limiting oxygen index test of the present invention refers to the standard "GB / T 2406.2-2009", the UL-94 vertical combustion test refers to the standard "GB / T 2408-2021", the maximum heat release rate test refers to the standard "ASTM D7309-21a", and the 90° peel strength test refers to the standard "ASTM D429-14". The maximum heat release rate is measured by a microcalorimeter.

[0019] The 30-day weight gain rate test method in the embodiment is as follows: the prepared cushioning material is placed in an indoor environment and weighed every day. The percentage of the weight increase after 30 days to the original weight is the 30-day weight gain rate. A stable 30-day weight gain rate indicates that the gel does not absorb moisture or dry, which indicates the stability of the product.

[0020] The 12h self-healing efficiency test method in the embodiment is as follows: two identical samples are taken from the prepared buffer material, one of which is used as the original sample to directly test its fracture stress, and the other is cut with a scalpel on its surface with a length of 1 cm and a depth of 1 cm, and then it is realigned. After standing at room temperature for 12 hours without applying any external force, its fracture stress is measured under the same conditions, and its percentage of the fracture stress of the original sample is the 12h self-healing efficiency. The fracture stress test refers to the standard "GB / T 1040.2-2022".

[0021] The 50% deformation compression strength test method is as follows: Use a universal testing machine to compress a 5cm thick sample to 50% of its original thickness and measure the stress.

[0022] The vertical drop test method in the embodiment is as follows: take a standard fire evidence sealing bag with a volume of 1L, fill it with 100 mesh quartz sand which accounts for 80% of the volume, seal it, and put the fire evidence sealing bag into a corrugated paper packaging box with a volume of 2L. The gap between the evidence sealing bag and the packaging box is filled with logistics transportation cushioning material of the same mass as the quartz sand. Seal the corrugated paper packaging box, release the packaging box vertically from a height of 3m, and let it fall; disassemble the packaging box and inspect the sealing bag. If there is no damage, the vertical drop test is passed, otherwise it is failed.

[0023] The melamine sponge sold on the market is applicable to the scheme of the present invention. The embodiment uses a density of 5kg / m 3 Melamine sponge is used as an example. The butadiene raw material in the embodiment is stored in a high-pressure tank in liquid form. When the sample is taken out under normal pressure, it becomes gaseous. When used, the gaseous butadiene will dissolve in the solvent. The preparation method of the self-healing fire evidence logistics transportation buffer material of the present invention is as follows Figure 1 shown.

[0024] The technical scheme of the present invention is clearly and completely described below in conjunction with the embodiments and the accompanying drawings. It should be pointed out that the embodiments described in the present invention are only used to further explain and illustrate, rather than to limit the scope of application. Based on the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0025] Example 1 The mass of the reaction liquid accounts for 35% of the buffer material S1. Take 0.91 g (0.0056 mol) of (4-vinylphenyl)dimethylsilane (CAS No.: 4556-72-3) and 29.61 g (0.1 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate, dissolve them in dichloromethane, add 0.30 g (0.0056 mol) of butadiene, and add 1.32 g (0.0059 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, and store it in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 50% of the mass of the reaction solution.

[0026] S2. Take 65g of melamine sponge, drip 35g of the above reaction solution evenly into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction solution, place it under a 650W ultraviolet lamp for 5 minutes, and perform primary polymerization; after the surface is dry, replace the backlight side with the light-facing side, and perform secondary light polymerization under ultraviolet lamp for 5 minutes; after aging in an oven at 50°C for 3 hours, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained. The scanning electron microscope image of the buffer material is as follows Figure 2 shown.

[0027] After testing, the prepared buffer material has a limiting oxygen index of 33.7%, a UL-94 vertical burning test that reaches V-0 level, a maximum heat release rate of 105.6W / g, a 30-day weight gain rate of 2.7%, a 90° peel strength (iron) of 2.91 N, a 12h self-healing efficiency of 36% at room temperature, a 50% deformation compression strength of 0.98 MPa, and a vertical drop test: passed.

[0028] Example 2 The mass of the reaction liquid accounts for 20% of the buffer material S1. Dissolve 32.42 g (0.2 mol) of (4-vinylphenyl)dimethylsilane and 7.40 g (0.025 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add 1.35 g (0.025 mol) of butadiene, and add 0.56 g (0.0025 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), dissolve and mix thoroughly to obtain a reaction solution, which is stored in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 80% of the mass of the reaction solution.

[0029] S2. Take 80g of melamine sponge, evenly drop 20g of the above reaction solution into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction solution, place it under a 650W ultraviolet lamp for 10 minutes to carry out primary polymerization; replace the backlight side with the light-facing side, carry out secondary light polymerization under an ultraviolet lamp for 10 minutes, and after aging at 100°C in an oven for 8 hours, obtain the self-healing fire evidence logistics transportation buffer material of the present invention.

[0030] After testing, the prepared buffer material has a limiting oxygen index of 33.7%, a UL-94 vertical burning test that reaches V-0 level, a maximum heat release rate of 136.7W / g, a 30-day weight gain rate of 2.91%, a 90° peel strength (iron) of 0.79N, a 12h self-healing efficiency of 33% at room temperature, a 50% deformation compression strength of 0.65 MPa, and a vertical drop test: passed.

[0031] Example 3 The mass of the reaction liquid accounts for 20% of the buffer material S1. Dissolve 10.21 g (0.063 mol) of (4-vinylphenyl)dimethylsilane and 56.26 g (0.19 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add 54.05 g (1 mol) of butadiene, and add 5.83 g (0.026 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), dissolve and mix thoroughly to obtain a reaction solution, which is stored in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 58% of the mass of the reaction solution.

[0032] S2. Take 200 g of melamine sponge, evenly drop 50 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 9 min to carry out primary polymerization; replace the backlight side with the light-facing side, carry out secondary light polymerization under ultraviolet lamp for 7 min, and after aging at 90° C. in an oven for 5 h, obtain the self-healing fire evidence logistics transportation buffer material of the present invention.

[0033] After testing, the prepared buffer material has a limiting oxygen index of 32.7%, a UL-94 vertical combustion test that reaches V-0 level, a maximum heat release rate of 121.2 W / g, a 30-day weight gain rate of 1.3%, a 90° peel strength (iron) of 1.38N, and a 12-hour self-healing efficiency at room temperature of Figure 3 Shown is 50%, 50% deformation compression strength 0.87MPa, vertical drop test: passed.

[0034] Example 4 The mass of the reaction liquid accounts for 30% of the buffer material S1. Dissolve 16.21 g (0.1 mol) of (4-vinylphenyl)dimethylsilane and 88.83 g (0.3 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add 32.43 g (0.6 mol) of butadiene, and add 6.95 g (0.031 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, which is stored in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 68% of the mass of the reaction solution.

[0035] S2. Take 210 g of melamine sponge, evenly drop 90 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 8 min to carry out primary polymerization; replace the backlight side with the light-facing side, and carry out secondary light polymerization under an ultraviolet lamp for 10 min; after aging at 80° C. in an oven for 7 h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0036] After testing, the prepared buffer material has a limiting oxygen index of 33.5%, a UL-94 vertical combustion test that reaches V-0, and a maximum heat release rate of Figure 4 The 90° peel strength on the iron surface is shown as 113.7 W / g, the weight gain rate in 30 days is 1.8%, and the Figure 5 As shown is 1.52 N, 12h self-healing efficiency at room temperature is 78%, 50% deformation compressive strength is 0.93 MPa, vertical drop test: passed.

[0037] Example 5 The mass of the reaction liquid accounts for 30% of the buffer material S1. Dissolve 56.73 (0.35 mol) of (4-vinylphenyl)dimethylsilane and 103.63 g (0.35 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add 16.22 g (0.3 mol) of butadiene, and add 3.36 g (0.015 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, which is stored in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 75% of the mass of the reaction solution.

[0038] S2. Take 210 g of melamine sponge, evenly drop 90 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 6 min to carry out primary polymerization; replace the backlight side with the light-facing side, and carry out secondary light polymerization under an ultraviolet lamp for 6 min; after aging at 60° C. in an oven for 5 h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0039] After testing, the prepared buffer material has a limiting oxygen index of 38.1%, a UL-94 vertical combustion test that reaches V-0, a maximum heat release rate of 81.5W / g, and a 30-day weight gain rate of Figure 6 The figure shows 0.1%. The 90° peel strength on the iron surface is as follows Figure 7 As shown is 1.82 N, 12h self-healing efficiency at room temperature is 92%, 50% deformation compressive strength is 1.17 MPa, vertical drop test: passed.

[0040] Comparative Example 1 The test data of ordinary melamine sponge (commercially available) are as follows: Limiting oxygen index 35.8%, UL-94 vertical burning test reaches V-0 level, maximum heat release rate 92.2W / g, 30-day weight gain rate 0.3%, 90° peel strength (iron) 0, 12h self-healing efficiency at room temperature 0, 50% deformation compression stress 53 KPa, vertical drop test: failed.

[0041] Comparative Example 2 S1. Dissolve 56.73 g (0.35 mol) of (4-vinylphenyl)dimethylsilane and 104.34 g (0.35 mol) of 1-butyl-3-ethylimidazole hexafluorophosphate (CAS: 256647-89-9) in dichloromethane, add 16.22 g (0.3 mol) of butadiene, and add 3.36 g (0.015 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, which is stored in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-butyl-3-ethylimidazole hexafluorophosphate and butadiene account for 75% of the mass of the reaction solution.

[0042] S2. Take 210 g of melamine sponge, evenly drop 90 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 6 min to carry out primary polymerization; replace the backlight side with the light-facing side, and carry out secondary light polymerization under an ultraviolet lamp for 6 min; after aging at 60° C. in an oven for 5 h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0043] After testing, the prepared buffer material has a limiting oxygen index of 31.2%, a UL-94 vertical burning test that reaches V-0 level, a maximum heat release rate of 167.7 W / g, a 30-day weight gain rate of 21.7%, a 90° peel strength on the iron surface of 0.57 N, a 12-hour self-healing efficiency of 10.6% at room temperature, a 50% deformation compression strength of 0.39 MPa, and a vertical drop test: failed.

[0044] Comparative Example 3 S1. Dissolve 36.42 (0.35 mol) of styrene and 103.63 g (0.35 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add 16.22 g (0.3 mol) of butadiene, and add 3.36 g (0.015 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, which is stored in an ice water bath; styrene, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 75% of the mass of the reaction solution.

[0045] S2. Take 210 g of melamine sponge, evenly drop 90 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 6 min to carry out primary polymerization; replace the backlight side with the light-facing side, and carry out secondary light polymerization under an ultraviolet lamp for 6 min; after aging at 60° C. in an oven for 5 h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0046] After testing, the prepared buffer material has a limiting oxygen index of 28.5%, a UL-94 vertical burning test that reaches V-1 level, a maximum heat release rate of 233.1 W / g, a 30-day weight gain rate of 3.7%, a 90° peel strength on the iron surface of 0.31 N, a 12h self-healing efficiency of 2.3% at room temperature, a 50% deformation compression strength of 0.75 MPa, and a vertical drop test: failed.

[0047] Comparative Example 4 S1. Dissolve 61.64 g (0.35 mol) of trimethyl (4-vinylphenyl) silane (CAS: 1009-43-4) and 103.63 g (0.35 mol) of 1-vinyl-3-butyl imidazole hexafluorophosphate in dichloromethane, add 16.22 g (0.3 mol) of butadiene, and add 3.36 g (0.015 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, which is stored in an ice water bath; trimethyl (4-vinylphenyl) silane, 1-vinyl-3-butyl imidazole hexafluorophosphate and butadiene account for 75% of the mass of the reaction solution.

[0048] S2. Take 210 g of melamine sponge, evenly drop 90 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 6 min to carry out primary polymerization; replace the backlight side with the light-facing side, and carry out secondary light polymerization under an ultraviolet lamp for 6 min; after aging at 60° C. in an oven for 5 h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0049] After testing, the prepared buffer material has a limiting oxygen index of 30.7%, a UL-94 vertical burning test that reaches V-0 level, a maximum heat release rate of 186.2 W / g, a 30-day weight gain rate of 5.5%, a 90° peel strength on the iron surface of 0.35 N, a 12h self-healing efficiency of 3.9% at room temperature, a 50% deformation compression strength of 0.63 MPa, and a vertical drop test: failed.

[0050] Comparative Example 5 S1. Dissolve 78.43 g (0.35 mol) of trimethoxy (4-vinylphenyl) silane (CAS: 18001-13-3) and 103.63 g (0.35 mol) of 1-vinyl-3-butyl imidazole hexafluorophosphate in dichloromethane, add 16.22 g (0.3 mol) of butadiene, and add 3.36 g (0.015 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), fully dissolve and mix to obtain a reaction solution, which is stored in an ice water bath; trimethoxy (4-vinylphenyl) silane, 1-vinyl-3-butyl imidazole hexafluorophosphate and butadiene account for 75% of the mass of the reaction solution.

[0051] S2. Take 210 g of melamine sponge, evenly drop 90 g of reaction liquid into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction liquid, place it under a 650 W ultraviolet lamp for 6 min to carry out primary polymerization; replace the backlight side with the light-facing side, and carry out secondary light polymerization under an ultraviolet lamp for 6 min; after aging at 60° C. in an oven for 5 h, the self-healing fire evidence logistics transportation buffer material of the present invention is obtained.

[0052] After testing, the prepared buffer material has a limiting oxygen index of 29.1%, a UL-94 vertical burning test that reaches V-1 level, a maximum heat release rate of 197.9 W / g, a 30-day weight gain rate of 7.2%, a 90° peel strength on the iron surface of 0.66 N, a 12-hour self-healing efficiency of 9.1% at room temperature, a 50% deformation compression strength of 0.82 MPa, and a vertical drop test: failed.

[0053] Comparative Example 6 S1. Dissolve 32.42 g (0.2 mol) of (4-vinylphenyl)dimethylsilane and 7.40 g (0.025 mol) of 1-vinyl-3-butylimidazole hexafluorophosphate in dichloromethane, add 1.35 g (0.025 mol) of butadiene, and add 0.56 g (0.0025 mol) of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator Irgacure-2959), dissolve and mix thoroughly to obtain a reaction solution, which is stored in an ice water bath; (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate and butadiene account for 80% of the mass of the reaction solution.

[0054] S2. Take 90g of melamine sponge, evenly drop 10g of the above reaction solution into it, slowly heat the system to room temperature after the sponge fully absorbs the reaction solution, place it under a 650W ultraviolet lamp for 10 minutes to carry out primary polymerization; replace the backlight side with the light-facing side, carry out secondary light polymerization under an ultraviolet lamp for 10 minutes, and after aging at 100°C in an oven for 8 hours, obtain the self-healing fire evidence logistics transportation buffer material of the present invention.

[0055] After testing, the prepared buffer material has a limiting oxygen index of 35.3%, a UL-94 vertical combustion test that reaches V-0 level, a maximum heat release rate of 97.1W / g, a 30-day weight gain rate of 0.3%, a 90° peel strength (iron) of 0.63N, and a 12-hour self-healing efficiency at room temperature of Figure 8 Shown are 20%, 50% deformation compression strength 0.16 MPa, vertical drop test: failed.

Claims

1. A self-healing fire evidence logistics transport buffer material, characterized in that: The buffer material is mainly composed of melamine sponge, imidazole compounds containing C=C bonds, silane compounds containing C=C bonds and Si-H bonds, and olefin compounds containing at least two C=C bonds.

2. The self-healing fire evidence logistics transport buffer material according to claim 1, characterized in that: The mass of melamine sponge in the buffer material accounts for 65% to 80%.

3. The self-healing fire evidence logistics transport buffer material according to claim 1, characterized in that: The imidazole compound containing a C=C bond includes 1-vinyl-3-butyl imidazole hexafluorophosphate ionic liquid, the silane compound containing a C=C bond and a Si-H bond includes (4-vinylphenyl) dimethylsilane, and the olefin compound containing at least two C=C bonds includes butadiene; the buffer material also contains a solvent and a photoinitiator.

4. The self-healing fire evidence logistics transport buffer material according to claim 3, characterized in that: The amounts of the materials in the buffer material are as follows: the molar ratio of (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate, and butadiene is (5-80): (10-90): (5-80).

5. The method for preparing the self-healing fire evidence logistics transport buffer material according to any one of claims 1 to 4, characterized in that: The method comprises the following contents: taking melamine sponge as a substrate, adding a reaction liquid into the substrate, and polymerizing imidazole compounds containing C=C bonds, silane compounds containing C=C bonds and Si-H bonds, and olefin compounds containing at least two C=C bonds in the reaction liquid in situ in the melamine sponge to obtain a fire evidence logistics transportation buffer material with self-healing and flame retardant functions.

6. The method for preparing the self-healing fire evidence logistics transport buffer material according to claim 3 or 4, characterized in that: Includes the following: S1. (4-vinylphenyl)dimethylsilane and 1-vinyl-3-butylimidazole hexafluorophosphate are dissolved in a solvent, and butadiene and a photoinitiator are added to obtain a reaction solution; S2: adding the above reaction liquid to the melamine sponge, and after the sponge fully absorbs the reaction liquid, irradiating it under a UV lamp to perform a primary light polymerization; replacing the backlight side with the light-facing side, and performing a secondary light polymerization under a UV lamp; and obtaining the buffer material after heat preservation and aging.

7. The method for preparing the self-healing fire evidence logistics transport buffer material according to claim 6, characterized in that: The amounts of the materials in step S1 are as follows: the molar ratio of (4-vinylphenyl)dimethylsilane, 1-vinyl-3-butylimidazole hexafluorophosphate, and butadiene is (5-80): (10-90): (5-80); the total mass of the above three materials accounts for 50%-80% of the total mass of the reaction solution; the molar amount of the photoinitiator accounts for 1%-5% of the total molar amount of the above three materials plus the photoinitiator.

8. The method for preparing the self-healing fire evidence logistics transport buffer material according to claim 6, characterized in that: In step S2, the mass of the melamine sponge accounts for 65% to 80% of the total mass of the buffer material, and the mass of the reaction liquid accounts for 20% to 35% of the total mass of the buffer material.

9. The method for preparing the self-healing fire evidence logistics transport buffer material according to claim 6, characterized in that: In step S1, the solvent includes dichloromethane, and the photoinitiator includes Irgacure-2959.

10. The method for preparing the self-healing fire evidence logistics transport buffer material according to claim 6, characterized in that: In step S2, the time of the first light polymerization is 5 min to 10 min, and the time of the second light polymerization is 5 min to 10 min; and the temperature is kept at 50° C. to 100° C. for 3 h to 8 h.

Citation Information

Patent Citations

  • Preparation method of environment-friendly type melamine-based foamed plastic

    CN109836548A

  • Articles comprising combinations of polymer aerogels and melamino-formaldehyde foams, and related systems and methods

    CN119365523A

  • Flame retardant additive for a low smoke, zero halogen compound

    US20190085154A1

Cited By

  • Caving risk early warning device for fire accident investigation

    CN121600670A